The Role of Motivation in the Influence of Transformational Leadership and Organizational Culture on Employee Performance: A Study at the Regional Secretariat of Solok City - Hilma Lathifah; Aldri Frinaldi (Khazanah Sosial, 2025)
This study aims to analyze the influence of transformational leadership and organizational culture on employee performance, with work motivation as a mediating variable, at the Regional Secretariat of Solok City. The research addresses challenges stemming from bureaucratic leadership styles and weak organizational culture, which are related to low employee motivation and performance. A quantitative method was employed, with data collected through surveys of 90 civil servants and analyzed using Structural Equation Modeling (SEM) assisted by SmartPLS. The results show that both transformational leadership and organizational culture have a positive and significant effect on employee motivation and performance. Motivation was found to mediate these relationships. This study emphasizes the importance of internal incentive systems, an adaptive work culture, and inspirational leadership in improving civil servant performance. These findings are expected to serve as a guideline for the Solok City Government in strengthening human resources and enhancing bureaucratic effectiveness.